2012
DOI: 10.1002/hep.24794
|View full text |Cite
|
Sign up to set email alerts
|

Family history of liver cancer and hepatocellular carcinoma

Abstract: Familial clustering of hepatocellular carcinoma (HCC) has been frequently reported in eastern Asiatic countries, where hepatitis B infection is common. Little is known about the relationship between family history of liver cancer and HCC in Western populations. We carried out a case-control study in Italy, involving 229 HCC cases and 431 hospital controls. Data on family history were summarized through a binary indicator (yes/no) and a family history score (FHscore), considering selected family characteristics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
86
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(100 citation statements)
references
References 41 publications
8
86
0
Order By: Relevance
“…Familial clustering of HCC cases is frequently observed, especially in Eastern countries, where HBV spread within the household is thought to be the reason why family history of HCC is a risk factor. A recent study also showed that a family history of liver cancer increases HCC risk independently of hepatitis even in a Western population [46].…”
Section: Risk Factors Of Hccmentioning
confidence: 93%
“…Familial clustering of HCC cases is frequently observed, especially in Eastern countries, where HBV spread within the household is thought to be the reason why family history of HCC is a risk factor. A recent study also showed that a family history of liver cancer increases HCC risk independently of hepatitis even in a Western population [46].…”
Section: Risk Factors Of Hccmentioning
confidence: 93%
“…20% of the individuals with NAFLD present with steatohepatitis, while the majority have steatosis only. Isolated steatosis of the liver probably has no effect on liver-related mortality [49,50,51]. …”
Section: Non-alcoholic Fatty Liver Diseasementioning
confidence: 99%
“…In line with this, the risk of developing HCC is higher in individuals with a family history of HCC [49]. A predisposing effect is being suggested for numerous single nucleotide polymorphisms (SNP).…”
Section: Host Factorsmentioning
confidence: 99%
“…Patients infected with HBV are known to be at an increased risk of developing HCC over their lifetime (3)(4)(5). Previous studies have reported familial aggregation of HCC (6,7), and previous meta-analyses have indicated that family history of HCC increases the risk of HCC in patients with viral hepatitis, independently of hepatitis (8). A previous study examined the effect of a family history of HCC on the incidence of HCC in the entire population who were screened for HBV seromarkers, and elucidated that family history of HCC multiplied the risk of HCC at each stage of HBV infection (7).…”
Section: Introductionmentioning
confidence: 99%